Evaluation of The Jalatista Tap Water Program at Universitas Padjadjaran - Tantan Gumilar (Universitas Muhammadiyah Semarang, 2023)
Introduction: Water is an essential natural resource for human life as almost 70% of the human body consists of water. In 2018, Universitas Padjadjaran had 32,481 students in which they require a lot of drinking water. This university has initiated a program called the Jalatista to provide drinking water. The result of a survey conducted by BEM Universitas Padjadjaran 2018 found that around 41,8% of students had never used the Jalatista. Methods: This research used mixed methods with a sequential explanatory design. The quantitative stage by conducting a survey involving 430 students and testing the microbiological quality of the drinking water at 10 points (20 water samples). The qualitative stage approach by conducting in-depth interviews with 2 managers. Results and Discussion: The result showed that in terms of context, the implementation of the Jalatista run quite well. The input aspect, it needed to increase the capacity of human resources and develop facilities so to make the program better. The process of socialization by the management was less optimal and lack of discipline in monitoring. The product aspect, students who have never used the Jalatista facility reached 52.8% (95% CI: 48.1% -57.5%), the quality of drinking water is still not suitable for drinking at 6 sample out of a total of 20 sample, and the level of user confidence is still found to be poor. Conclusion: The Jalatista program must pay great attention to the aspect of maintenance to improve the quality of drinking water produced at all points.